Recover Overnight? Work Interruption and Worker Productivity - Cai, Xiqian; Gong, Jie; Lu, Yi; Zhong, Songfa (Management Science, 2018)
This paper investigates the effect of work interruption on workers’ subsequent productivity. We employ a data set of individual productivity and machine conditions, in which each worker faces the chance, on a daily basis, that her machine will break down randomly. Our analysis finds that compared to a workday with smooth production, experiencing a machine breakdown is associated with a 3.3 percentage point decline in the worker’s productivity the following day. We discuss possible explanations for the observed effect, including negative emotions, increased cautiousness in operating the machine, and proficiency loss. Our findings shed light on the importance of understanding and managing interruptions in the workplace, and contribute to a growing literature on the determinants of productivity at the micro level. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2792 . This paper was accepted by John List, behavioral economics.